xCT knockdown in human breast cancer cells delays onset of cancer-induced bone pain - Ungard, Robert G (Mol Pain, 2019)
Cancers in the bone produce a number of severe symptoms including pain that compromises patient functional status, quality of life, and survival. The source of this pain is multifaceted and includes factors secreted from tumor cells. Malignant cells release the neurotransmitter and cell-signaling molecule glutamate via the oxidative stress-related cystine/glutamate antiporter, system x(C)(−), which reciprocally imports cystine for synthesis of glutathione and the cystine/cysteine redox cycle. Pharmacological inhibition of system x(C)(−) has shown success in reducing and delaying the onset of cancer pain-related behavior in mouse models. This investigation describes the development of a stable siRNA-induced knockdown of the functional trans-membrane system x(C)(−) subunit xCT (SLC7A11) in the human breast cancer cell line MDA-MB-231. Clones were verified for xCT knockdown at the transcript, protein, and functional levels. RNAseq was performed on a representative clone to comprehensively examine the transcriptional cellular signature in response to xCT knockdown, identifying multiple differentially regulated factors relevant to cancer pain including nerve growth factor, interleukin-1, and colony-stimulating factor-1. Mice were inoculated intrafemorally and recordings of pain-related behaviors including weight bearing, mechanical withdrawal, and limb use were performed. Animals implanted with xCT knockdown cancer cells displayed a delay until the onset of nociceptive behaviors relative to control cells. These results add to the body of evidence suggesting that a reduction in glutamate release from cancers in bone by inhibition of the system x(C)(−) transporter may decrease the severe and intractable pain associated with bone metastases.